Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 13566 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Gyps coprotheres (J.R.Forster, 1798)" ] } The dataset includes 13566 records from 22 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003317-150912100344238/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences